Exploring the Link Between Cephalosporin Antibiotic Use and Urolithiasis: A Case–Control Study - R. Gandhimathi, (Asian Journal of Pharmaceutics (AJP), 2024)
Purpose: The study aimed to explore the association between cephalosporin antibiotics and urolithiasis, specifically focusing on Oxalobacter formigenes ( O. formigenes) a colonization process. Materials and Methods: An observation was made that 50 were among patients, with kidney stones and 110 without stones had participated in the study. O. formigenes, a bacterium known to metabolize oxalates in the gastrointestinal tract, was detected in 36 of the 50 kidney stone patients and in 97 of the 110 control participants. Results: It was found that calcium and oxalate levels in urine. There was a significant increase in kidney stone patients than in controls, suggesting that these elevated levels may contribute to stone formation. Given the sensitivity of O. formigenes to certain antibiotics, including cephalosporins, frequent antibiotic use may reduce O. formigenes. This reduction could lead to increased oxalate absorption, as O. formigenes is not present to metabolize oxalates effectively. Conclusion: Thereby heightening Formation of kidney stones is at risk. According to these findings, the absence or reduction of species colonization may contribute to calcium oxalate stone pathogenesis, especially in patients taking antibiotics such as cephalosporins. Consequently, this study highlights the need for cautious antibiotic use to preserve beneficial gut microbiota, which assists protecting against diagnosis and treatment of kidney stones. Further research could confirm these associations and guide antibiotic stewardship practices to prevent disruptions in gut microbiome balance that might contribute to urolithiasis.